Change in Practice of Radioactive Iodine Administration in Differentiated Thyroid Cancer: A Single-Centre Experience. Issue 5 (25th July 2021) - Wijewardene, Ayanthi; Gild, Matti; Nylén, Carolina; Schembri, Geoffrey; Roach, Paul; Hoang, Jeremy; Aniss, Ahmad; Glover, Anthony; Sywak, Mark; Sidhu, Stan; Learoyd, Diana; Robinson, Bruce; et al.
Abstract : Objective: Our study aimed to analyse temporal trends in radioactive iodine (RAI) treatment for thyroid cancer over the past decade; to analyse key factors associated with clinical decisions in RAI dosing; and to confirm lower activities of RAI for low-risk patients were not associated with an increased risk of recurrence. Methods: Retrospective analysis of 1, 323 patients who received RAI at a quaternary centre in Australia between 2008 and 2018 was performed. Prospectively collected data included age, gender, histology, and American Joint Committee on Cancer stage (7th ed). American Thyroid Association risk was calculated retrospectively. Results: The median activities of RAI administered to low-risk patients decreased from 3.85 GBq (104 mCi) in 2008–2016 to 2.0 GBq (54 mCi) in 2017–2018. The principal driver of this change was an increased use of 1 GBq (27 mCi) from 1.3% of prescriptions in 2008–2011 to 18.5% in 2017–2018. In patients assigned as low risk per ATA stratification, lower activities of 1 GBq or 2 GBq (27 mCi or 54 mCi) were not associated with an increased risk of recurrence. In patients assigned to intermediate- or high-risk categories who received RAI as adjuvant therapy, there was no difference in risk of recurrence between 4 GBq (108 mCi) and 6 GBq (162 mCi). Conclusions: Our data demonstrate an evolution of RAI activities consistent with translation of ATA guidelines into clinical practice. Use of lower RAI activities was not associated with an increase in recurrence in low-risk thyroid cancer patients. Our data also suggest lower RAI activities may be as efficacious for adjuvant therapy in intermediate- and high-risk patients.